2010
DOI: 10.2105/ajph.2009.165449
|View full text |Cite
|
Sign up to set email alerts
|

Social Network Structure of a Large Online Community for Smoking Cessation

Abstract: Objectives We evaluated the social network structure of QuitNet, one of the largest online communities for behavior change, and compared its characteristics to other known social networks. Methods Using modern network analysis methods, we identified QuitNet members who were active during a 60-day period, along with their ties. We then derived multiple subgroups, such as key players and integrators, from connections and communication patterns. Results Among 7569 participants, we identified 103592 connection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
183
0
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 194 publications
(196 citation statements)
references
References 38 publications
9
183
0
4
Order By: Relevance
“…18 QuitNet incorporates evidence-based elements of tobacco dependence treatment 20 including practical counseling for cessation, pharmacotherapy information, and intratreatment social support through a large online social network. 21 Participants randomized to EI + P also had 6-month free access to QuitNet plus five proactive telephone counseling calls provided by National Jewish Health. Participants randomized to BI had 6-month free access to an information-only comparison condition comprised of the major content on QuitNet: information about cessation ("Quitting Guide") and pharmacotherapy ("Medication Guide"), a directory of national cessation programs, and a 10-year database of Frequently Asked Questions (FAQs).…”
Section: Interventionsmentioning
confidence: 99%
“…18 QuitNet incorporates evidence-based elements of tobacco dependence treatment 20 including practical counseling for cessation, pharmacotherapy information, and intratreatment social support through a large online social network. 21 Participants randomized to EI + P also had 6-month free access to QuitNet plus five proactive telephone counseling calls provided by National Jewish Health. Participants randomized to BI had 6-month free access to an information-only comparison condition comprised of the major content on QuitNet: information about cessation ("Quitting Guide") and pharmacotherapy ("Medication Guide"), a directory of national cessation programs, and a 10-year database of Frequently Asked Questions (FAQs).…”
Section: Interventionsmentioning
confidence: 99%
“…Indeed, research suggests that gun violence is intensely concentrated within high-risk populations. 10,11 For example, recent studies in Boston found that from 1980 to 2008, only 5 % of city block faces and street corners experienced 74 % of gun assault incidents 12 and that 50 % of homicide and nearly 75 % of gun assaults were driven by less than 1 % of the city's youth population (aged [15][16][17][18][19][20][21][22][23][24], most of whom were gang involved and chronic offenders. 13 To better understand how gunshot injury is distributed within highrisk populations, we conducted a study to determine whether the risk of gunshot victimization is related to characteristics of one's social networks.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17] There are several reasons why the risk of gunshot victimization is related to one's social network. First, interpersonal violence tends to occur between people who know each other suggesting that the context of social relationships is important in understanding the dynamics of gun violence.…”
Section: Introductionmentioning
confidence: 99%
“…However, few studies have investigated the interactive and reciprocal nature of support exchange in online support forums (e.g., Cobb, Graham, & Abrams, 2010;Manago, Taylor, & Greenfield, 2012). Drawing on the theoretical framework of social capital and adopting social network analysis, the current study examines the reciprocal nature of communication in online support forums.…”
mentioning
confidence: 99%